A guide to wireless networking by light. (September 2017) - Haas, Harald; Chen, Cheng; O'Brien, Dominic
Abstract: The lack of wireless spectrum in the radio frequency bands has led to a rapid growth in research in wireless networking using light, known as LiFi (light fidelity). In this paper an overview of the subsystems, challenges and techniques required to achieve this is presented.